IMPACT OF SOCIO-ECONOMIC STATUS AND CAMPUS ENVIRONMENT ON STUDENTS' CUMULATIVE ACHIEVEMENT INDEX OF ZAINUL HASAN ISLAMIC UNIVERSITY, GENGGONG KRAKSAAN, PROBOLINGGO - Abd Aziz; Moh. Abd. Rahman (Faculty of Islamic Economics and Business, 2022)
The research aims to see the influence of the campus environment on IPK, the influence status social econony to IPK as wellthe as inof fluence eon nvironment campus and socioeconomic status against IPK. This research is a descriptive research associative quantitative. The population in this study were undergraduate students Islamic Religious Education Faculty of Tarbiyah Zainul Hasan Islamic University Genggong Kraksaan Probolinggo year 2022 . Total populis ation as many as 137 students. The samples taken were 103 people. The analysis technique used is analysis regression simple and regression double. Results study shows that 1. socioeconomic status has no significant effecstudentsA student of the Department of Islamic Religious Education Faculty of Tarbiyah UNZAH, 2. no campus environan ment take effect significant to IPK student Major Islamic Religious Education Faculty of T,arbiyah UNZAH, and 3 socio-economic status and campus environment have no effect significant to IPK student Major Islamic Religious EducationFaculty of Tarbiyah UNZAH.